(untitled) (Homoeopathy for All, 2024)
In later childhood stage the psychological complaints, such as apprehension, despondency and PTSD (post-traumatic stress disorder) inclined to occur. Mostly these are hard to be identified initially by the guardians or the others as some babies have not originated significant vocabulary and cognition to demonstrate their feelings.